Enhancing the ballistic resistance of steel/aluminum bilayer armor plates through explosive welding - Qibo Zhang; Ye Yuan; Chengjian Zhang; Yufeng Zhang; Pengwan Chen (Materials & Design, 2023)
This work presents a comprehensive analysis of the ballistic response of Q235 steel/6061-T6 aluminum bilayer plates fabricated via explosive welding, with a special focus placed on elucidating the mechanisms of ballistic resistance enhancement due to the bonded interface. For comparison purposes, unbonded Q235 steel/6061-T6 aluminum bilayer plates (e.g. being stacked together or spaced with an air gap) were also investigated. Ballistic tests were carried out to compare the residual velocities and failure behaviours of the welded and unwelded bilayer plates. Computational models were built in LS/DYNA and validated with the experiment. Experimental results showed that the ballistic limit velocity of the explosively-welded plate is 13.4% and 9.4% higher than those of the in-contact plate and air-gapped plate. Simulation results suggested that the enhanced ballistic resistance was attributed to its welded interface. On the one hand, the welded interface allowed effective stress attenuation within the steel layer leading to a greater damage tolerance and more energy dissipation during the prolonged response time. On the other hand, when deforming together with the steel layer, the welded interface enforced a uniform indentation on the central region of the aluminum substrate leading to greater energy absorption due to compression and thinning of the material.